The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1965
DOI: 10.1111/j.1476-5381.1965.tb01769.x
|View full text |Cite
|
Sign up to set email alerts
|

On the Mechanism of Action of Guanethidine and Bretylium

Abstract: Guanethidine is often thought to act like bretylium and produce sympathetic blockade by interfering with the process by which nerve impulses invade sympathetic nerve terminals (Boura & Green, 1959;Cass & Spriggs, 1961). Guanethidine, in contrast to bretylium, impairs the capacity of tissues to store noradrenaline (Sheppard & Zimmerman, 1959;Cass, Kuntzman & Brodie, 1960), but this action of the drug is usually dismissed as distinct from its bretylium-like action since the degree of blockade does not parallel t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
23
0

Year Published

1967
1967
2000
2000

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(30 citation statements)
references
References 14 publications
7
23
0
Order By: Relevance
“…Guanethidine appears to produce a persistent depolarization in adrenergic nerve endings, thereby leading to the blockade. This idea is consistent with the hypothesis of Chang et al (1965) and Brodie et al (1965).…”
Section: Resultssupporting
confidence: 82%
“…Guanethidine appears to produce a persistent depolarization in adrenergic nerve endings, thereby leading to the blockade. This idea is consistent with the hypothesis of Chang et al (1965) and Brodie et al (1965).…”
Section: Resultssupporting
confidence: 82%
“…creased V,,,,, and action potential height. The guanethidine molecule is apparently too large to pass through sodium channels in an ionized form, as suggested by Hille's experiments (1971) (Schanker & Morrison, 1965;Brodie et al, 1965). Membrane depolarization after transient excitation in adrenergic nerve endings seems to be mainly responsible for the blockade, because the adrenergic neurone blocking action in rabbit hearts depends upon the external sodium concentrations (Kubo & Misu, 1974).…”
Section: Effects Ofpretreatment With a Low Dose Of Tetrodotoxin On Gumentioning
confidence: 94%
“…Many hypotheses have been advanced concerning the mechanism by which adrenergic neurone blocking drugs prevent the release of noradrenaline (Boura & Green, 1965;Brodie, Chang & Costa, 1965;Burn & Welsh, 1967;Abbs & Dodd, 1974;Kubo & Misu, 1974;Giachetti & Hollenbeck, 1976). Kubo & Misu (1974) demonstrated that guanethidine-induced blockade of adrenergic transmission in rabbit hearts is attenuated when nerves are stimulated during perfusion with a low sodium solution and accentuated during perfusion with a high sodium solution.…”
Section: Introduction Methodsmentioning
confidence: 99%
“…Our results are in agreement with previous findings of Kirpekar & Furchgott (1964) who showed that cocaine antagonizes the inotropic effect of bretylium on normal guinea-pig left atrium. Brodie, Chang & Costa (1965) have shown that bretylium uptake by rat heart in vivo decreases by about 32% in animals previously treated with cocaine. Although our results on restoration of tyramine response do not allow us to measure exactly the degree of blockade of bretylium uptake, the fact that cocaine when present during bretylium treatment completely abolished the restoration of the response to tyramine, suggests that blockade must be appreciable.…”
Section: Discussionmentioning
confidence: 99%